Effect of hydrogen-rich water on periodontal disease, interleukin and blood glucose levels in diabetic - Albert Manggading HUTAPEA; Lina HADI (Dentistry Faculty, 2021)
ABSTRACT Diabetes Mellitus (DM) is a metabolic disorder characterized by high blood glucose levelsassociated with periodontal disease and increased levels of inflammatory biomarkers such asinterleukin. Therapeutic effects of molecular hydrogen for a wide range of disease models and humandiseases have been investigated. This review aims to systematically analyze and review animal andhuman studies investigating the effect of HRW on periodontal tissues, interleukin, or blood glucoselevels. An electronic search was conducted via PubMed/Medline, Google Scholar, Wiley Online Library,LILACS, Science.gov, and Cochrane Central Register of Controlled Trials (CONTROL) using thekeywords